Excess body fat and associated factors: A study of newcomers to a public university in Northeastern Brazil (Research, Society and Development, 2022)
The purpose of this study was to evaluate the occurrence of excess body fat and its associated factors in freshman from a public university in the Northeast of Brazil. This is a cross-sectional analytical study involving 231 freshman with body fat percentage evaluated by electrical bioimpedance, being defined as excess values above 15% for men and 23% for women. The conceptual model considered sociodemographic, anthropometric, dietary and lifestyle variables. The results showed a predominantly female sample (71,4%), mean age of 20.0 ± 4.2 years and 53,7% belonging to the middle class. It was evidenced a high prevalence of excess body fat (48,0%) and after adjustment for Poisson Regression, were independently associated with excess body fat: overweight, abdominal obesity, body perception of being above weight and the use of food in stress situations. The high prevalence of excess body fat is a warning given the youth of the population evaluated and shows the need to insist on primary and secondary prevention measures.